Transatlantic Textbooks: Karl Hagenbach, Shared Interests, and German Academic Theology in Nineteenth-Century America. Issue 3 (31st July 2014) - Purvis, Zachary
<x content-type="archive" xml:space="preserve">Abstract</x> The rise of German academic institutions in the nineteenth century considerably altered the landscape of American higher education. American students of theology looked to Germany to develop their discipline, where they found model textbooks that gave directives in learning and piety, transforming academic and theological practice. With sensitivity to the history of the book and the history of the rich cultural traffic across the Atlantic, this article focuses on the reception in English translation of the important and widely read Swiss-German church historian Karl Rudolf Hagenbach, whose textbooks enjoyed a considerable audience in the United States by crossing ideological boundaries and unseating obdurate assumptions. By examining this reception in the United States and Britain and investigating those "transatlantic personalities" who played pivotal roles in bringing his ideas from the "Old World" to the "New, " this article demonstrates Hagenbach's lasting influence on the changing fields of history, church history, and academic theology in America. An "Atlantic" perspective on these themes offers new insights for our understanding of religion in the modern academy, the movement and translation of theological ideas in an age of steamship travel, and the surfacing of commonalities among ostensibly mismatched, if not outright conflicting, Protestant religious cultures.